Evaluating the Potential of Agarose Hydrogel Incorporating Eggshell Powder as a Sustainable Medium for Seedling Growth - Nuryantini, Ade Yeti; Mahen, Ea Cahya Septia; Oktaviani, Indri; Nuryadin, Bebeh Wahid; Edikresnha, Dhewa; Khairurrijal, Khairurrijal (Pandawa Institute, 2026)
Hydrogels represent a promising alternative for plant cultivation, offering excellent water and nutrient retention. This study reports the synthesis and characterization of an agarose-based hydrogel composite enhanced with eggshell powder (ESP). The hydrogel composites were prepared in four agarose-to-ESP ratios: 10:0 (Hyd-ES0), 10:1 (Hyd-ES1), 10:3 (Hyd-ES3), and 10:5 (Hyd-ES5). Fourier-transform infrared spectroscopy (FTIR) analysis revealed minimal peak shifts, indicating no significant chemical modifications. Characteristic ESP peaks were identified in the composite hydrogels, confirming the effective integration of ESP into the agarose matrix. The addition of ESP reduced the decomposition rate of the hydrogels and increased macromolecular stability. Density measurements indicated higher density with increasing ESP concentration, supported by enhanced crystal formation, as evidenced by more intense diffraction peaks in X-ray diffraction (XRD) patterns. Morphological analysis revealed that the porosity of the hydrogel, swelling, and weight-loss tests showed a decline in both properties with higher ESP content. Seed germination experiments demonstrated that stem, root, and leaf growth, as well as fresh and dry weights, were most optimal with the Hyd-ES1 hydrogel composite. Thus, Hyd-ES1 hydrogel exhibits significant potential as a medium for seed germination and plant growth.